Designing a Thermochemistry E-Module Based on the Trait Treatment Interaction Educational Model for Madrasah Aliyah Students - Aswirna, Prima; Wardani, Titisma; Asrar, Allan; Fahmi, Reza; Fahmi, Danial Muhammad (Jurnal Tadris Kimiya, 2024)
Planning and carrying out investigations (PCOI) among students are still low, and teachers pay less attention to differences in the abilities of each student, so they have not achieved optimal results. This research aims to develop of a chemistry e-module using the trait treatment interaction (TTI) model to increase valid, practical, and effective's PCOI capabilities. TTI is considered an ideal learning model because it can accommodate and value individual differences among students. The research framework employed in this study follows a research and development method with a define, design, development, and disseminate (4D) model. The results indicate that the high validity level achieved an average score of 84.3% in terms of materials, language, and media aspects. The practicality test of the products also received an average score of 86.2%. The product's effectiveness is categorized as very effective, with students' test results averaging 82.3%. The e-module is deemed valid, practical, and effective in enhancing PCOI capabilities.